Proceedings of the 15th International Joint Conference on Computer Vision, Imaging and Computer Graphics Theory and Application 2020
DOI: 10.5220/0009153902730280
|View full text |Cite
|
Sign up to set email alerts
|

A Taxonomy of Treemap Visualization Techniques

Abstract: A treemap is a visualization that has been specifically designed to facilitate the exploration of tree-structured data and, more general, hierarchically structured data. The family of visualization techniques that use a visual metaphor for parent-child relationships based "on the property of containment" (Johnson, 1993) is commonly referred to as treemaps. However, as the number of variations of treemaps grows, it becomes increasingly important to distinguish clearly between techniques and their specific chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 60 publications
0
14
0
Order By: Relevance
“…However, some of these are too specific or not related to our purpose. For example, researchers in [28] propose a taxonomy specifically for static (i.e., non interactive) visualizations, whilst other specific taxonomies have been proposed for dynamic graph visualizations [29], [30] and treemap visualizations [31]. The taxonomy proposed by Guimarães et al [21] is closely related to our work.…”
Section: ) Use Of Existing Taxonomies For Analyzing the Extracted Datamentioning
confidence: 72%
“…However, some of these are too specific or not related to our purpose. For example, researchers in [28] propose a taxonomy specifically for static (i.e., non interactive) visualizations, whilst other specific taxonomies have been proposed for dynamic graph visualizations [29], [30] and treemap visualizations [31]. The taxonomy proposed by Guimarães et al [21] is closely related to our work.…”
Section: ) Use Of Existing Taxonomies For Analyzing the Extracted Datamentioning
confidence: 72%
“…A visualisation called a tree map [ 92 ] was created expressly to make it easier to explore data that are organised hierarchically and in trees. The research trend, debate gaps, and related fields that would be of interest as research areas could all be identified using this data.…”
Section: Bibliometric Analysis and Resultsmentioning
confidence: 99%
“…Including visualizations that focus on object-oriented software quality and comprehension, the SeeSoft [32] tool visualization maps lines of code into thin rows, uses colors to display information about the timeframe where the code has changed. Scheibel et al, [33] propose a treemap visualization depicting software data using areas, colors and nesting. Additionally, Lanza's et al, present CodeCrawler [14] that supports the understanding of program structure via polymeric views.…”
Section: Related Workmentioning
confidence: 99%